Microstructure and mechanical properties of a novel Mg–RE–Zn–Y alloy fabricated by rheo-squeeze casting. (15th March 2016) - Fang, Xiaogang; Lü, Shulin; Zhao, Li; Wang, Jing; Liu, Longfei; Wu, Shusen
Abstract: The refinement of the microstructure and uniform distribution of RE-rich intermetallic compounds are beneficial for strengthening and toughening the rare earth (RE) containing Mg alloy castings. A novel Mg–3RE–6Zn–1.4Y alloy was designed, and fabricated by rheo-squeeze casting (RSC) in this research. The semi-solid slurry used in the process was treated by direct ultrasonic vibration (DUV) and then casted with squeeze casting. The microstructure evolution and mechanical properties of the RSC alloy with different pressures were investigated. The RE-rich intermetallic compounds were analysed by X-ray diffraction (XRD), energy dispersive spectrometer (EDS) and transmission electron microscope (TEM). The results indicate that the increase of the pressure not only contributes to the refinement of α-Mg grains but also results in the increasing solid solubility in the matrix and uniform distribution of RE-rich intermetallic compounds along the grain boundary. The tensile properties increase continuously with the increase of applied pressure. The yield strength (YS), ultimate tensile strength (UTS) and elongation of RSC sample under 200 MPa pressure are 110 MPa, 180 MPa and 8.6%, which are improved by 17.0%, 19.2% and 81.7% respectively than the corresponding values of the samples without pressure. Graphical abstract: Highlights: A novel Mg–3RE–6Zn–1.4Y magnesium alloy was designed. Phase constitutions were distinguished including I, W and T phase. Increase of pressure refined α-Mg phase and increased solid solubility. RE-rich intermetallic compounds were homogenized and refined under high pressure.